(untitled) (Stato, Chiese e pluralismo confessionale, 2024)
Religiously oriented eating styles and sustainability in the legal experience of the territories facing the Mediterranean Sea ABSTRACT: The paper presents the different eating styles created by religious confessions, which were born in the territories facing the Mediterranean Sea, and by oriental religions, which have also taken root in Europe. Some problems that arise in the exercise of religious food freedom within civil legal systems are analyzed. The interrelationships between political institutions, religious confessions and communities ethically committed to sustainable development are studied, in order to use the different food codes to more effectively pursue the unitary objective of improving the health and well-being of living beings in the Euro-Mediterranean area, of wisely exploit environmental resources and redistribute food more equitably. SOMMARIO: 1. Il cibo nei territori prospicienti il Mar Mediterraneo tra pluralismo etnico-religioso e biodiversità - 2. I diversi codici alimentari delle religioni mediterranee - 3. I rapporti fra ordinamenti civili e religiosi in ordine alla libertà religiosa alimentare - 4. Diritto al cibo, diritto dell’ambiente ed ecologia integrale fra sistemi giuridici religiosi e umanesimi non confessionali - 5. I novel food e i tentativi di greenwashing - 6. La sostenibilità del cibo per “alimentare” il laico sogno europeo di unità nella diversità.